Integrating transformative learning theory in synchronous E-learning in musculoskeletal pain education among primary care nurses: a randomized study - Khim Siong Ng; Zhi Yin Tang; Pang Nee Frida Wong; Joo Ling Joanne Chua; Li Lin Lydia Goh; Yi Ling Eileen Koh; Kim Hwee Koh (BMC Nursing)
Abstract Background Synchronous E-learning has been used in Continuing Professional Education (CPE) to teach nurses about musculoskeletal (MSK) pain, but it is insufficient to achieve deeper conceptualization. Hence, we applied Transformative Learning Theory (TLT) to complement the CPE. This study aimed to assess the effectiveness of the TLT-design CPE and explore the learners’ experience of transformative learning in synchronous E-learning. Methods A multicenter randomized controlled trial design was employed. Participants received synchronous E-learning CPE, either in the TLT-design workshop (intervention group) or in the usual didactic workshop (control group). Data collection was conducted before, immediately after, and one month after the workshop. We used validated outcome measures, namely, Neurophysiology of Pain Questionnaire (NPQ), Management Advice Vignette (MAV), and Health Care Pain Attitudes and Impairment Relationship Scale (HC-PAIRS). Additionally, narrative comments and feedback were gathered. Baseline comparisons were assessed using independent t-tests and repeated measures ANOVA for the three time points. Generalized Estimating Equations (GEE) were used for intention-to-treat analysis, incorporating multiple covariates. Significance was set at p < 0.05. Cohen’s d was reported as a measure of effect size. Results Both groups showed significant improvements, and the effects were sustained after one month. However, the GEE model showed that the intervention group had significantly improved scores in NPQ compared to the control group (p = 0.006). In addition, the intervention group performed significantly better in MAV (p = 0.008, d = 0.528) and HC-PAIRS (p = 0.046, d=-0.390) after one month. Participants’ narrative comments and feedback supported the transformative learning experience. They also expressed a preference for face-to-face teaching, shorter didactic sessions, and more interactive activities of longer duration. Conclusions Synchronous E-learning is effective for teaching MSK pain. When enhanced with TLT design, learners showed significant and sustained improvements. Deliberate application of TLT strategies should be considered in pain education. Practical recommendations are provided to further enhance the teaching of MSK pain. Additional strategies should be explored to reinforce the learning of pain knowledge. Trial registration Registered on ClinicalTrials.gov registry (NCT05589311) on 21 October 2022. First recruitment was on 24 October 2022.